The eye-popping world of financial accounting - Mattingly, Christopher; Deege, Robert; Canant, C. Alan.; Torgeson, Igor.; Standard Deviants (Performing group); Cerebellum Corporation; Goldhil Educational (Firm) ([Arlington, Va.] : Cerebellum Corp. ; [Camarillo, CA] : Goldhil Educational [Distributor], 2005)
Covers the important concepts, problems and processes in accounting.
program 1. Basics -- program 2. Using ledgers -- program 3. Accounting tools -- program 4. Income statements -- program 5. Preparing an income statement -- program 6. Applications -- program 7. Business accounting -- program 8. Account management.
Videographer, Alpesh Patel; editor, Mind & Media.
Standard Deviants.
DVD.
Keywords: Accounting; Financial statements